Analisis Nilai Tambah Asam Gelugur Menjadi Asam Potong (Studi Kasus Desa Alue Drien Kecamatan Birem Bayeun Kabupaten Aceh Timur) - Dinda Sixtiara; Muhammad Jamil; Faoeza Hafiz Saragih (Jurnal Penelitian Agrisamudra, 2021)
This study aims to analyze the benefits and added value of gelugur acid into cut acid in Alue Drien Village, Birem Bayeun District, East Aceh Regency. This research was conducted in Alue Drien Village, Birem Bayeun District, East Aceh Regency. The data used in this study is to use primary data and secondary data. To analyze the profit and added value of gelugur acid into cut acid in Alue Drien Village, Birem Bayeun District, East Aceh Regency, we used the Profit Analysis Method and the Hayami Method. The results of this study indicate that the amount of revenue obtained from the sale of cut acid products is Rp. 24,000,000. The total cost incurred during the production process is Rp. 8,985,200. So that a profit of Rp. 15,014,800. And the processed gelugur acid into cut acid provides added value, and the results are added value with an added value ratio of 55%.